1979
DOI: 10.1093/oxfordjournals.jbchem.a132645
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of an Active Lysozyme Derivative: Kyn 62-Lysozyme1

Abstract: A novel method for the preparation of Kyn 62-lysozyme, in which tryptophan 62 is replaced by kynurenine, is reported. Hen egg-white lysozyme was ozonized in aqueous solution to yield one N'-formylkynurenine residue and deformylated with hydrochloric acid in frozen solution at -10 degrees C. Crude Kyn 62-lysozyme was purified by affinity and Bio Rex 70 chromatography successively. Kyn 62-lysozyme retains affinity for chitin and is essentially an active enzyme with a slightly weakened but distinct catalytic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Although the Trp residue can be oxidized by chemical and physical agents (e.g. ozone, metal and ionizing radiation) [21,22], the Trp to Kyn44 conversion may be catalysed by endogenous enzyme(s). Note that tryptophan pyrrolooxygenase, catalysing Trp oxidation, was identified in plants, bacteria and mammals [23–26].…”
Section: Discussionmentioning
confidence: 99%
“…Although the Trp residue can be oxidized by chemical and physical agents (e.g. ozone, metal and ionizing radiation) [21,22], the Trp to Kyn44 conversion may be catalysed by endogenous enzyme(s). Note that tryptophan pyrrolooxygenase, catalysing Trp oxidation, was identified in plants, bacteria and mammals [23–26].…”
Section: Discussionmentioning
confidence: 99%
“…HEWL was purchased from Seikagaku Kogyo Co. Kyn62-lysozyme was prepared with the methods of Yamasaki et al 5 ) Tri-N-acetyl-D-glucosamine «GlcNAch) and L-tryptophan were purchased from Sigma Chemical Co.…”
Section: Methodsmentioning
confidence: 99%
“…S ) This derivative has fairly high enzymatic activity and an absorption maximum at 360 nm. 4 ) In a previous work, we demonstrated that the binding of (GlcNAc)3 to Kyn 62-lysozyme induced the red shift of tryptophan and kynurenine, producing a UVdifference spectrum with maxima at 293 and 390nm. S ) These findings directed us to shed further light on the active site of lysozyme using spectroscopic characteristics of Kyn 62-lysozyme.…”
mentioning
confidence: 88%